Structural changes in the economy of the Russian North-West regions: institutional factor - Oleg V.Tolstoguzov (Baltic Region, 2022)
Balancing out uneven regional development and territorial disparities is an urgent task. Solving it requires considering the geo-economic features of various parts of Russia’s spatially structured territory. This study aims to describe trends in the economic space transformation and structural changes in the economies of the North-Western Federal District. Exploring the economic space transformation, the paper draws on economic theory and geography, the concepts of cluster and power generation cycles, regional economics and other theories. It presents the results of the institutional and economic research of income capitalization and the role of the institutional factor, along with regional gross value added (GVA) analysis by activity types. The study investigates the movement of capital (rent) in the economic space. There are several noticeable trends: the Arkhangelsk and Murmansk regions, the Komi and Karelia Republics have diversified their economies by developing manufacturing and mining, while the Murmansk and Pskov regions did that by stimulating agriculture. Regional factors generating rent at significant transaction costs are found to be affected by institutional factors. The paper concludes that structural changes in the economy of the Russian north-west regions are wavelike in nature. The indexes of regional GVA and industrial market development point to the existence of a transition zone between the structural phases of the wave, with the transition mostly taking place in 2014. The trigger for the second phase of the wave, along with new structural changes, was international sanctions and growing confrontation reducing capital outflow and contributing to further structural changes in the regional economy.